Evaluation of the Sustainable Use of Land Resources in the Cities along the Jiangsu Section of the Beijing–Hangzhou Grand Canal - Fei Shi; Yuanyuan Lu; Longgao Chen; Wei-Ling Hsu (Land, 2023)
Sustainable development is an important topic of urban research. The rational use of land resources is of great significance for urban development and is conducive to promoting regional governance and coordinated development. The purpose of this study was to construct an effective evaluation framework for urban land resources to maintain sustainable urban development. Taking the cities along the Jiangsu Section of the Beijing–Hangzhou Grand Canal as the research object, this study constructed an evaluation system for the sustainable use of land resources including the dimensions of economic level, social development, and environmental resources. The statistical data for 2010, 2015, and 2020 were selected to comprehensively calculate and evaluate the level of sustainable use of land resources in the study area via the analytic hierarchy process (AHP)-entropy combined weight method, which combines the analytic hierarchy process and the entropy weight method. According to the research results, the sustainable use of land resources in the study area presented an overall upward trend from 2010 to 2015, and an overall downward trend from 2015 to 2020. Overall, the study area was in a critically sustainable stage, although the annual change rate of the level of sustainable use of land resources showed significant fluctuations and exhibited a spatial pattern of progressive increase from north to south. The cities in southern Jiangsu were in the initially sustainable and basically sustainable stages; those in central Jiangsu were in the critically sustainable and initially sustainable stages; and those in northern Jiangsu were in the unsustainable and critically sustainable stages. This study proposed a scientific and effective evaluation method for cities along the Grand Canal to explore the efficient, sustainable use of land resources in the future. The evaluation framework constructed on this basis can serve as an important reference for urban governance and is expected to guide the sustainable use and development of land resources for other cities of the same type.